Analysis of the effectiveness of instructional recommendations for forming practical skills and abilities in adolescents - Irina R. Gainutdinova (Saratov State University, 2021)
Lessons for forming practical skills and abilities are significant in the educational process. A laboratory lesson, as the main type of lessons for forming practical skills and abilities, is linked to a number of difficulties in organizing effective work of adolescent schoolchildren. The purpose of the study is to experimentally check the effectiveness of the developed instructional recommendations for forming practical skills and abilities in adolescents, taking into account age and gender role characteristics. The hypothesis of the study is: the developed instructional recommendations increase the effectiveness of development of practical skills and abilities in adolescent schoolchildren. The study substantiates the necessity of using the knowledge of age and gender-role characteristics of schoolchildren by a teacher in organizing and conducting laboratory lessons. The study also highlights the methodological research principles, i.e. individually differentiated and holistic approach to teaching schoolchildren. The study is carried out on a sample of 8th grade students (N = 52, aged from 13 to 14 years; experimental group (n = 25), control group (n = 27)) of the educational institution "Gymnasium No. 1" in Saratov. We carried out inter-group analysis of average grade points of schoolchildren for laboratory works in physics, chemistry and biology during the 2018-2019 academic year using the Mann - Whitney U test. It showed that the developed instructional recommendations contribute to an increase in the effectiveness of the formation of practical skills and abilities in adolescents, while not significantly affecting the average grade points. The applied aspect of the problem under study can be implemented in the development of a complex of pedagogical strategies that ensure the effectiveness of the formation of practical skills and abilities in adolescent schoolchildren during laboratory lessons.